Penyuluhan Pengetahuan Tentang Instalasi Listrik dan Mengoptimalkan Penggunaannya Serta Mengatasi Bahaya Listrik Bagi Masyarakat Di Wilayah Duri Kosambi, Cengkareng Jakarta Barat - Christine Widyastuti; Isworo Pujotomo; Muchammad Nur Qosim; Rinna Hariyati; Aas Wasri Hasanah; Oktaria Handayani; Tony Koerniawan (Sekolah Tinggi Teknik - PLN, 2020)
Electricity is the most suitable and appropriate form of energy for modern human life, such as today, where electrical energy has a function that can provide a need or service for electric power obtained by consumers, with electricity human life becomes very pleasant. Television, lighting, traffic lights, all using electricity. So, electricity can be said as a form of technological results that are very vital in human life. With this activity, it is expected that the general public can and understand about safe electrical installation and handling, mitigation of electrical hazards that are not in accordance with PLN's standardization. So that electricity does not necessarily become a scapegoat every time there is a fire in the community, and the voltage system used in Indonesia is: single phase 220 V, and phase three 220/380 V with a frequency of 50 Hz. This voltage system is very influential and dangerous for human safety.